119k views
0 votes
Y=x​2​​−6x+10​
y=4−x​​


How do I substitute?

User Anchandra
by
5.6k points

1 Answer

2 votes

Answer:

(2,2) and (3,1)

Explanation:

Since we're given the value of y in the second equation, we can replace the y on the left side of the first equation with 4-x, giving us


4-x=x^2-6x+10\\0=x^2-5x+6

We can factor the expression on the right to get us


0=x^2-5x+6\\0=x^2-3x-2x+6\\0=x(x-3)-2(x-3)\\0=(x-2)(x-3)

Solving
x-2=0 and
x-3=0 gets us the solutions
x=2,3, which we can plug into the second equation to get us


y=4-2=2\\y=4-3=1

So, our solution set is the pair of points (2,2) and (3,1)

User Kasmira
by
5.9k points